Le milieu d’artistes dans "La Force du désir" de Krysinska - Wierzbowska, Ewa M. (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
Marie Krysinska’s novel, La Force du désir, for the longest time was read as a roman à clef, an ironic depiction of the Parisian artistic milieu. Krysinska, a composer, poet, and a writer, exposes a society riddled with hypocrisy. The work of art is valued not by its merits, but by its popularity or by the sex of the creator, and, consequently, a mediocre male artisan achieves recognition for his work, while a true female artist – only a compliment on her beauty. In the artistic realm, a woman is the Other, Stranger, just like those male creators who do not submit themselves to doxa. Krysinska’s novel depicts the struggle and endurance of Art and the artist, suppressed by a mediocre audience and its false idols.